2017
DOI: 10.18043/ncm.78.4.223
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Rates and Cause of Death Among Former Prison Inmates in North Carolina

Abstract: background Inmates face challenges upon release from prison, including increased risk of death. We examine mortality among former inmates in North Carolina, including both violent and nonviolent deaths. methods A retrospective cohort study among former North Carolina inmates released between 2008 and 2010 were linked with North Carolina mortality data to determine cause of death. Inmates were followed through December 31, 2012. Mortality rates among former inmates were compared with deaths among North Carolina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Two, 18, and four studies examined federal, state, and local correctional facilities, respectively (sum is greater than 20 as some studies included multiple levels of government). Only five of the 20 studies used data that was less than 10 years old as of 2021 7,16–19 . Except in studies sharing datasets (e.g., Spaulding et al 10 and Zlotorynzska et al 12 ), studies used incompatible methodologies, data sources, time periods, and patient populations that prevent direct quantitative comparisons of study findings.…”
Section: Resultsmentioning
confidence: 99%
“…Two, 18, and four studies examined federal, state, and local correctional facilities, respectively (sum is greater than 20 as some studies included multiple levels of government). Only five of the 20 studies used data that was less than 10 years old as of 2021 7,16–19 . Except in studies sharing datasets (e.g., Spaulding et al 10 and Zlotorynzska et al 12 ), studies used incompatible methodologies, data sources, time periods, and patient populations that prevent direct quantitative comparisons of study findings.…”
Section: Resultsmentioning
confidence: 99%
“…There is evidence to suggest, for example, that health deficits after release are common, and there may even be a greater risk of death. In North Carolina (USA) 6 and France 7 , higher mortality rates of 2% and 3.6% respectively, have been observed amongst ex-convicts than amongst the general public; in the French study 7 this mortality was most common in the younger population, from 30 to 50 years of age.…”
Section: Health Services and Fairnessmentioning
confidence: 87%
“…Amongst the factors related to increased mortality after release from prison is abuse of heroin and other opiates [8][9][10][11][12][13] , alcohol abuse is another factor, along with treatment with antidepressants in prison or recidivism, while some other factors such as being married may act as a protective factor 8 . Although the main cause of death after release is from overdose, the potential causes are numerous 6 and include chronic organic pathologies (cancer or heart disease), infectious diseases (such as HIV) 14 , or acts of violence (suicide, homicide or accidents). Many of the causes may be potentially preventable, but there is little information about the health and behaviour of the persons at risk, which makes it difficult establish evidentially-based preventive responses.…”
Section: Health Services and Fairnessmentioning
confidence: 99%
“…Although the risk of cardiovascular morbidity and mortality among former prisoners has received less attention than that of other causes, existing studies suggest that (as in the general population), cardiovascular disease is among the leading causes of death for people released from prison [10,11]. For example, a study of incarcerated people released from Washington state prisons between 1999 and 2009 [21] found that following overdose, cardiovascular disease was the second leading cause of death (13%), and in a North Carolina study, the risk of death from heart disease among formerly incarcerated people was 4.5 times that of the general population [22]. Despite these findings, less than 30% (N = 14) of state prison systems reportedly target cardiovascular disease for continuity of care, and the North Carolina prison system has been among those not supporting this continuity [12].…”
Section: Discussionmentioning
confidence: 99%